Anatomical observations of female internal genitalia in three eulophids associated to Eucalyptus (Hymenoptera Chalcidoidea) (Bollettino di zoologia agraria e bachicoltura, 2024)
Material was obtained from leaves or capsules of Eucalyptus camaldulensis Dehnh. in Southern Italy; it refers to 3 species, identified by Dr. J. La Salle (CSIRO Entomology, Canberra) as follows: Ophelimus maskelli (Ashmead, 1900), Leptocybe invasa Fisher & La Salle, 2004, and Quadrastichodella nova Girault, 1922. Conspicuous interspecific variations were detected concerning egg shape andglandular equipment. Egg shape is typically "hymenopteroid" in O. maskelli, "pedunculate" in L. invasa and Q. nova. Glandular equipment includes: (i) a single gland in O. maskelli and Q. nova, referred as ovipositor gland; (ii) a pair of glands in L. invasa and Q. nova, referred as oviduct glands. As it does not agree with the rule in Eulophidae, the author thinks that the particular glandular equipment in the examined eulophids does depend on the parthenogenetic reproduction and/or on the phytophagous diet.
Keywords: ovarioles; egg types; glands; spermatheca; Ophelimus maskelli (Ashmead); Leptocybe invasa Fisher & La Salle; Quadrastichodella nova Girault